Structural accreditation of healthcare facilities: comparison of the requirements by Italian Presidential Decree 14/01/1997 and regional regulations. A proposal for updating the minimum environmental units at national level: A proposal for updating the minimum environmental units at national level - Gola, Marco; Sapienza , Martina; Slama, Faris; Brundu , Laura; Campus, Roberta; Manai , Stefano; Nicosanti, Roberto; Ogana , Silvia; Orrù, Marco; Ortu, Giovanni Maria; Piga , Giulia; La Milia , Daniele Ignazio; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim. The Decree of the President of the Italian Republic 14/01/1997 is the reference norm related to the accreditation of public and private healthcare structures. This guideline establishes the minimum structural, technological and organizational requirements that each structure operating in the Italian territory must comply with. Methods. In occasion of the project work for the postgraduate training course in healthcare management by ALTEMS School, a team of researchers conducted a survey on the state of updating of the minimum structural requirements indicated in the norm-in particular those relating to hospital facilities- with those adopted by the individual regions through the analysis of the most up-to-date regional regulations. Results. Precisely starting from the comparison of regional references and from the regulations on the subject of structural accreditation which suggest strategic environmental units and which address some key-aspects relating to the contemporary design of healing environments (i.e. semi-intensive care units, hybrid operating theatres, etc.), the outcome of the project work is to define a proposal to update the national reference document, also in the light of the currently changing needs in terms of hospital design. Conclusions. The research aims to become a starting milestone for future investigations. The team investigated – in this first phase – the functional areas listed in the norm, and the next step aims to extend the analysis also to the innovative functions (i.e. buffer spaces, hybrid operating theatres, sub-intensive care units, etc.) and/or introduced only the last years which have only been regulated in some regions.